Extract of Rhus verniciflua Bark Suppresses 2,4-Dinitrofluorobenzene-Induced Allergic Contact Dermatitis - Park, Dong Ki (Hindawi Publishing Corporation, 2013)
Rhus verniciflua Stokes (RV) has traditionally been used as a food supplement and a traditional herbal medicine for centuries in Korea. Recent studies suggest that RV has potent antioxidative, antitumor, and anti-inflammatory properties. In this study, the anti-inflammatory effects of RV from mice sensitized with 2,4-dinitrofluorobenzene (DNFB) and activated macrophages were investigated. The results showed that RV reduced ear swelling and hyperplasia of ear tissue as well as an increase in vascular permeability, which are characteristics of allergic contact dermatitis (ACD) with evident histomorphological changes in epidermis and dermis. Decreased numbers of infiltrated mast cells were seen in RV extract treated group, using toluidine blue staining. RV extract significantly regulates the expression of inducible nitric oxide synthase (iNOS) at the translational level in activated macrophages. Furthermore, RV extract and its active compound, fisetin, attenuated the level of tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6) mRNA in LPS-stimulated macrophages. Anti-ACD effect of RV extract may be due to the suppression of iNOS and proinflammatory cytokines which might be mediated via the NFκB signaling pathways. Collectively, RV extract has potential for alleviating ACD-like symptoms induced by DNFB in the mouse.